A Critical Analysis of the Role of Lexicographers as Translators in Bilingual Lexicography- A Study Based on Peter Percival’s Tamil-English Dictionary - Sheliyna, S. (Faculty of Arts University of Jaffna, Sri Lanka, 2022)
Indicating the meaning of words is the most important task of a lexicographer. The branch of Linguistics that deals with meaning is called semantics. It is necessary for a lexicographer to be familiar with semantic concepts in order to produce translation equivalents for a dictionary. The compiler of a bilingual dictionary should make adequate use of the cultural information in her/his/their description of meanings. An attempt is, therefore, made to study the problems that the compiler of a bilingual dictionary faces in presenting meaning. These problems can be categorized under the following topics: the lack of equivalence in the Target Language, culture-bound words, onomasiological gaps and sense discrimination in bilingual dictionaries. In all these problems, translation plays a vital role with different procedures. Therefore, the study analyses the problems in Bilingual-Lexicography based on the second re-printed version (2000) of Peter Percival’s bilingual dictionary (Tamil-English) which was published by the Asian Educational Services, New Delhi. The findings of the study indicate that certain translation procedures including synonyms, descriptive equivalence, transliteration and cultural substitution were widely applied in composing the dictionary to produce equivalents for the easy reference of users. The words which were in use in the 19th century were included in the dictionary. According to the findings, the translation procedures handled by Peter Percival were brilliant. This study will the help reader to become familiar with Peter Percival’s contribution to the field of Translation and to the people of Jaffna during his period. Further, this study is expected to enrich the understanding of researchers who focus on the role of lexicographers as translators in the compilation of bilingual lexicons particularly in the Tamil and English languages.
Keywords: Bilingual- Dictionary; Lexicography; Procedures; Target language; Translators